Prestimulus oscillations predict visual perception performance between and within subjects - Hanslmayr, Simon; Aslan, Alp; Staudigl, Tobias; Klimesch, Wolfgang; Herrmann, Christoph S.; Bäuml, Karl-Heinz (NeuroImage (Orlando, Fla.), 2007)
In the present study, the electrophysiological correlates of perceiving shortly presented visual stimuli are examined. In particular, we investigated the differences in the prestimulus EEG between subjects who were able to discriminate between four shortly presented stimuli (Perceivers) and subjects who were not (Non-Perceivers). Additionally, we investigated the differences between the subjects perceived and unperceived trials. The results show that Perceivers exhibited lower prestimulus alpha power than Non-Perceivers. Analysis of the prestimulus EEG between perceived and unperceived trials revealed that the perception of a stimulus is related to low phase coupling in the alpha frequency range (8–12 Hz) and high phase coupling in the beta and gamma frequency range (20–45 Hz). Single trial analyses showed that perception performance can be predicted by phase coupling in the alpha, beta and gamma frequency range. The findings indicate that synchronous oscillations in the alpha frequency band inhibit the perception of shortly presented stimuli whereas synchrony in higher frequency ranges (> 20 Hz) enhances visual perception. We conclude that alpha, beta and gamma oscillations indicate the attentional state of a subject and thus are able to predict perception performance on a single trial basis.